High-conductivity liquid metal composite material and preparation method and application thereof
By combining zinc-based metal organic frame material with liquid metal, the problem of reducing conductivity and processing difficulty of liquid metal in flexible wearable devices is solved, high conductivity and good processability are achieved, and its performance in electrochemical applications is improved.
Patent Information
- Application Number
- CN202411892000.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
AI Technical Summary
The application of liquid metals in flexible wearable devices is limited by reduced conductivity, difficult processing, insufficient stability and oxidation ease.
The zinc-based metal organic frame material is used to combine with liquid metal, and MOF-Zn1 is prepared by coordination polymerization method, and it is mixed into the liquid metal to form a highly conductive liquid metal composite material.
It improves the conductivity of composite materials, enhances its application capabilities in the field of electrochemistry, and provides stable support through porous structures, improving the processability and stability of liquid metals.
Smart Images

Figure CN119753470A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of liquid metal materials, and in particular to a high-conductivity liquid metal composite material and a preparation method and application thereof. Background Art
[0002] Liquid metal is a metal material that is liquid at room temperature or lower temperature and has unique physical and chemical properties. Its main characteristics include low melting point, high thermal conductivity / electrical conductivity, high deformability and excellent electrochemical properties. Flexible wearable devices generally refer to electronic devices that can fit the curves of the human body and are flexible and wearable. The high deformability, conductivity and biocompatibility of liquid metal have led to its rapid development in flexible wearable devices.
[0003] However, to successfully apply liquid metal to flexible wearable devices, some key issues need to be resolved. For example, liquid metal is difficult to process, making it difficult to manufacture complex shapes and structures, and its stability needs to be further improved. In addition, liquid metal is easily oxidized at room temperature to form an oxide layer, which affects its fluidity and conductivity. These issues limit the application of liquid metal in flexible wearable devices. Summary of the invention
[0004] The present invention aims to solve the problem of reduced conductivity when liquid metal composite materials are currently used in flexible wearable devices.
[0005] In order to solve the above problems, the present invention provides a high-conductivity liquid metal composite material and a preparation method and application thereof.
[0006] As a first aspect, the present invention relates to a high-conductivity liquid metal composite material, wherein the high-conductivity liquid metal composite material comprises a zinc-based metal organic framework material and a liquid metal, and the zinc-based metal organic framework material is prepared by the following method:
[0007] The zinc salt and 5-((4'-(tetrazolyl-5'-yl)benzyl)oxy)isophthalic acid are dissolved in a reaction solvent, stirred and mixed evenly, dried, cooled to room temperature, and ground to obtain a zinc-based metal organic framework material.
[0008] Optionally, the zinc-based metal organic framework material comprises the following elements in percentage by mass: C: 50% to 55%, N: 5% to 7%, O: 15% to 20%, and Zn: 20% to 25%.
[0009] Optionally, the particle size of the zinc-based metal organic framework material is between 40 μm and 200 μm.
[0010] Optionally, the molar ratio of the zinc salt to the 5-((4'-(tetrazolyl-5'-yl)benzyl)oxy)isophthalic acid is 2:1 to 2.5:1.
[0011] Optionally, the reaction solvent is an acetonitrile aqueous solution, and the volume concentration of the acetonitrile aqueous solution is 50% to 70%;
[0012] And / or, the zinc salt is zinc nitrate, zinc chloride, zinc acetate and corresponding crystalline hydrated zinc salts.
[0013] Optionally, the drying includes: drying at 120° C. to 150° C. for 90 h to 100 h.
[0014] Optionally, the liquid metal includes eutectic gallium-indium alloy and / or eutectic gallium-indium-tin alloy.
[0015] In a second aspect, the present invention also relates to a method for preparing a liquid metal composite material, which is used to prepare the above-mentioned liquid metal composite material, comprising:
[0016] The liquid metal is first ultrasonically stirred for 40s to 50s, and then the zinc-based metal organic framework material is mixed with the liquid metal and ultrasonically stirred for 60s to 70s to obtain a liquid metal composite material.
[0017] Optionally, the mass ratio of the zinc-based metal organic framework material and the liquid metal when mixed is 1:(100-300).
[0018] In a third aspect, the present invention also relates to the application of the above-mentioned liquid metal composite material in flexible wearable devices.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention adopts 5-((4'-(tetrazolyl-5'-yl)benzyl)oxy)isophthalic acid as an organic ligand, undergoes coordination polymerization with a zinc salt, and adopts a solvothermal method to prepare a zinc-based metal organic framework material (MOF-Zn1). The zinc-based metal organic framework material is then incorporated into liquid metal to give play to the advantages of both and create a composite material with unique properties. Among them, the liquid metal has high conductivity, which can improve the electron transmission ability of MOF-Zn1, thereby enhancing its application in the field of electrochemistry. In addition, the high fluidity and plasticity of the liquid metal can give MOF-Zn1 better flexibility, allowing it to adapt to different shapes and stress conditions. The porous structure of MOF-Zn1 can provide stable support for the liquid metal, prevent it from agglomerating or losing during use, and make the liquid metal easier to process into different forms and structures. In addition, the mass proportion of MOF-Zn1 in the liquid metal composite material is about 0.3%-1%, and MOF-Zn1 is interconnected in the form of fine particles and evenly dispersed in the liquid metal matrix, forming a continuous conductive network, which makes the synthesized liquid metal composite material have excellent electrical conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is an electron microscope scanning image of the zinc-based metal organic framework material in Example 1 of the present invention;
[0022] Figure 2 is an element distribution diagram of the zinc-based metal organic framework material in Example 1 of the present invention;
[0023] Figure 3 is a flow chart of the preparation of the liquid metal composite material in Example 1 of the present invention;
[0024] Figure 4 is a micro-computed tomography image of the liquid metal composite material in Example 1 of the present invention;
[0025] Figure 5 A summary diagram of the electrical conductivity of the liquid metal composite material in Examples 1-3 of the present invention;
[0026] Figure 6 It is a summary of the solid-state fluorescence spectra of each material in Examples 1-3 and Comparative Examples 1-3;
[0027] Figure 7 It is a comparison chart of the electrical conductivity of the liquid metal composite materials in Example 1 and Comparative Examples 4-7. DETAILED DESCRIPTION
[0028] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. Although certain embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be interpreted as being limited to the embodiments described herein. On the contrary, these embodiments are provided to provide a more thorough and complete understanding of the present invention. It should be understood that the drawings and embodiments of the present invention are only for exemplary purposes and are not intended to limit the scope of protection of the present invention.
[0029] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by those skilled in the art to which this application belongs; the terms used in the specification of this application are only for the purpose of describing specific implementation methods and are not intended to limit this application;
[0030] The term "including" and its variations used in this article are open inclusions, that is, "including but not limited to"; the term "based on" is "based at least in part on"; the term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one other embodiment"; the term "some embodiments" means "at least some embodiments"; the term "optionally" means "optional embodiments". The relevant definitions of other terms will be given in the following description. It should be noted that the concepts of "first" and "second" mentioned in the present invention are used to distinguish different objects, rather than to describe a specific order or a primary and secondary relationship. In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise specified, the meaning of "multiple" is two or more.
[0031] At present, the mechanical properties and stability of liquid metal can be improved by compounding it with other materials, such as preparing liquid metal / polymer-based composite materials. However, in some polymer-based liquid metal composite materials, if the liquid metal is not specially treated, it may form discrete tiny droplets and cannot form a continuous conductive network, which reduces the conductivity of the composite material.
[0032] Metal-organic framework materials (MOFs) are a type of crystalline porous materials with a periodic network structure formed by self-assembly of metal ions or metal clusters and organic ligands through coordination bonds. Due to their unique thermal stability, water resistivity and significant chemical stability, they are widely used in gas adsorption and separation, catalysis, energy and drug delivery. MOFs have the characteristics of high specific surface area, adjustable pore structure and diverse chemical composition, which makes them have the advantage of being used as sensors in flexible wearable devices to detect various physiological indicators or environmental parameters.
[0033] MOFs materials generally have low flexibility and high brittleness, which makes MOFs materials difficult to process, especially making them into thin films or other desired shapes, thus limiting their application in flexible wearable devices.
[0034] Based on the above related technologies, the inventors found that the composite material obtained by compounding MOFs materials and liquid metals can produce unexpected effects, which is expected to improve the problems existing in its application in flexible wearable devices. Based on this discovery, the present invention provides a highly conductive liquid metal composite material and its preparation method and application.
[0035] In a first aspect, the present invention provides a highly conductive liquid metal composite material, wherein the liquid metal composite material comprises a zinc-based metal organic framework material and liquid metal, wherein the zinc-based metal organic framework material is prepared by the following method: dissolving a zinc salt and 5-((4'-(tetrazolyl-5'-yl)benzyl)oxy)isophthalic acid in a reaction solvent, stirring and mixing them evenly, drying, cooling to room temperature, and grinding to obtain the zinc-based metal organic framework material.
[0036] The present invention adopts 5-((4'-(tetrazolyl-5'-yl)benzyl)oxy)isophthalic acid as an organic ligand, undergoes coordination polymerization with a zinc salt, and adopts a solvothermal method to prepare a zinc-based metal organic framework material (MOF-Zn1). The zinc-based metal organic framework material is then incorporated into liquid metal to give play to the advantages of both and create a composite material with unique properties. Among them, the liquid metal has high conductivity, which can improve the electron transmission ability of MOF-Zn1, thereby enhancing its application in the field of electrochemistry. In addition, the high fluidity and plasticity of the liquid metal can give MOF-Zn1 better flexibility, allowing it to adapt to different shapes and stress conditions. The porous structure of MOF-Zn1 can provide stable support for the liquid metal, prevent it from agglomerating or losing during use, and make the liquid metal easier to process into different forms and structures. In addition, the mass proportion of MOF-Zn1 in the liquid metal composite material is about 0.3%-1%, and MOF-Zn1 is interconnected in the form of fine particles and evenly dispersed in the liquid metal matrix, forming a continuous conductive network, which makes the synthesized liquid metal composite material have excellent electrical conductivity.
[0037] In the embodiment of the present invention, the molecular structure of 5-((4'-(tetrazolyl-5'-yl)benzyl)oxy)isophthalic acid is shown in formula (I):
[0038]
[0039] As can be seen from formula (I), the ligand includes an isophthalic acid portion and a tetrazole group. The isophthalic acid portion is a benzene ring containing two carboxyl groups, which are located at the 1 and 3 positions of the benzene ring, i.e., the meta position. This structure enables the compound to participate in a variety of coordination chemical reactions and form a variety of supramolecular structures. The tetrazole group provides the ability to coordinate with other metal ions to form a stable complex. The presence of the tetrazole group gives the compound good thermal stability, allowing it to maintain structural integrity at higher temperatures.
[0040] Optionally, the liquid metal in the high-conductivity liquid metal composite material includes eutectic gallium-indium alloy and / or eutectic gallium-indium-tin alloy. Among them, the eutectic gallium-indium alloy is a eutectic alloy composed of two elements, gallium and indium, and the eutectic gallium-indium-tin alloy is a silver-white liquid metal synthesized from three low-melting-point metal elements, gallium, indium and tin. Both the eutectic gallium-indium alloy and the eutectic gallium-indium-tin alloy are liquid at room temperature. In one specific embodiment, the mass fraction of gallium in the eutectic gallium-indium alloy is 75%, and the mass fraction of indium is 25%.
[0041] Optionally, the zinc salt is specifically zinc nitrate, zinc chloride, zinc acetate and corresponding crystalline hydrated zinc salts, such as Zn(NO3)2·6H2O.
[0042] In some optional embodiments, the reaction solvent can be an acetonitrile aqueous solution, and the volume concentration of the acetonitrile aqueous solution is 50% to 70%. Acetonitrile has a strong dissolving ability, which helps to fully mix the reactants, thereby improving the reaction efficiency. Of course, in other embodiments, the reaction solvent can also be ethanol, methanol, acetone, dimethylformamide or N,N-dimethylacetamide, etc.
[0043] Optionally, the molar ratio of the zinc salt to the 5-((4'-(tetrazolyl-5'-yl)benzyl)oxy)isophthalic acid is 2:1 to 2.5:1. By adjusting the ratio of the zinc salt to the organic ligand, the structural stability and rigidity of the zinc-based metal organic framework material can be improved.
[0044] Optionally, the zinc salt and 5-((4'-(tetrazolyl-5'-yl)benzyl)oxy)isophthalic acid are dissolved in an acetonitrile aqueous solution, stirred and mixed evenly, and then dried at 120°C to 150°C for 90h to 100h. Then cooled to room temperature and ground to obtain a zinc-based metal organic framework material. By controlling the drying conditions, the uniformity of the final structure of the product can be improved, and a more consistent and controllable zinc-based metal organic framework material can be obtained.
[0045] Optionally, the zinc-based metal organic framework material includes four elements: C, N, O, and Zn, wherein the mass percentage of C is 50% to 55%, the mass percentage of N is 5% to 7%, the mass percentage of O is 15% to 20%, and the mass percentage of Zn is 20% to 25%. In addition, according to the results shown in the scanning electron microscope image, it can be observed that after drying and grinding, the particle size of the zinc-based metal organic framework material is mainly distributed between 40 μm and 200 μm.
[0046] As a second aspect, the present invention also relates to a method for preparing a highly conductive liquid metal composite material, which is used to prepare the above-mentioned highly conductive liquid metal composite material. Specifically, the method comprises: firstly ultrasonically stirring the liquid metal for 40s to 50s, then mixing the zinc-based metal organic framework material with the liquid metal, and ultrasonically stirring for 60s to 70s to obtain the liquid metal composite material. The mass ratio of the zinc-based metal organic framework material to the liquid metal when mixed is 1: (100-300), and the power of the ultrasonic stirring is 700-800W.
[0047] In the embodiment of the present invention, the liquid metal and the zinc-based metal organic framework material only need to be ultrasonically stirred for 100s to 120s to prepare a highly conductive liquid metal composite material. During the stirring process, the zinc-based metal organic framework material is evenly dispersed in the liquid metal, and the re-integrated liquid metal matrix completely wraps the zinc-based metal organic framework material. The preparation process of the liquid metal composite material in the present invention is simple, the reaction conditions are mild, and it is conducive to large-scale production.
[0048] As a third aspect, the present invention also relates to the application of the above-mentioned highly conductive liquid metal composite material in flexible wearable devices. The composite material combined with liquid metal and MOF-Zn1 inherits the high thermal conductivity / conductivity of liquid metal and the high porosity of MOF-Zn1. The highly conductive liquid metal composite material can be made into a complex three-dimensional structure through 3D printing technology, and further used as a material for components such as sensors in flexible wearable devices.
[0049] The present invention is described in detail below through specific examples and comparative examples:
[0050] Example 1
[0051] (I) Preparation of Zn-based Metal-Organic Framework Materials
[0052] Solid powders of 5-((4'-(tetrazolyl-5'-yl)benzyl)oxy)isophthalic acid and Zn(NO3)2·6H2O were dissolved in a 62.5% acetonitrile aqueous solution at a molar ratio of 1:2. Stir at room temperature for 30 minutes to mix evenly, and then transfer the mixed solution to a 20mL Teflon reactor. The reactor was placed in a constant temperature oven at 120°C and dried for 96 hours, then cooled to room temperature and ground to obtain a zinc-based metal organic framework material.
[0053] The electron microscope scanning image of the zinc-based metal organic framework material in this embodiment is as follows Figure 1 The element distribution diagram is shown in Figure 2 As shown. Figure 1 It can be observed that after dry grinding, the particle size of the Zn-based MOF materials ranges from 40 μm to 200 μm. Figure 2 It can be found that the zinc-based metal organic framework material in this embodiment includes four elements: Zn, C, N, and O, and the mass percentage of each element is: Zn: 23.38%, C: 54.05%, N: 6.12%, O: 16.45%. Then, with 340nm ultraviolet light as excitation, the solid-state fluorescence spectrum of the zinc-based metal organic framework material in Example 1 is obtained.
[0054] (II) Preparation of highly conductive liquid metal composite materials
[0055] The specific preparation process of highly conductive liquid metal composite materials is as follows: Figure 3 As shown, Figure 3In the figure, MOF-Zn1 represents a zinc-based metal organic framework material, and EGaIn represents a eutectic gallium-indium alloy. Specifically, the eutectic gallium-indium alloy is poured into a beaker and ultrasonically stirred for 40 seconds, and then the zinc-based metal organic framework material prepared in this embodiment (I) is dispersed in the eutectic gallium-indium alloy, and then ultrasonically stirred for 60 seconds to obtain a highly conductive liquid metal composite material, and finally the highly conductive liquid metal composite material is transferred to a culture dish for storage. Among them, the mass ratio of the zinc-based metal organic framework material and the liquid metal when mixed is 1:100, the mass fraction of gallium in the eutectic gallium-indium alloy is 75%, the mass fraction of indium is 25%, and the ultrasonic power of the ultrasonic stirring is 700W-800W.
[0056] In order to verify the microscopic distribution of eutectic gallium-indium alloy phase and MOF-Zn1 phase in the highly conductive liquid metal composite material, micro-computed tomography scanning of the liquid metal composite material was performed using an X-ray microscope. Figure 4 The density difference between MOF-Zn1 and liquid metal is intuitively demonstrated in the figure, revealing the structural characteristics of the liquid metal composite material. Figure 4 As shown in the figure, in a cube with a side length of 1800 μm, the distribution of the two phases is clearly visible. Among them, the MOF-Zn1 phase (blue part) is interconnected in the form of fine particles and evenly dispersed in the liquid metal (gray part) matrix, forming a continuous conductive network.
[0057] Example 2
[0058] (I) Preparation of Zn-based Metal-Organic Framework Materials
[0059] The solid powders of 5-((4'-(tetrazolyl-5'-yl)benzyl)oxy)isophthalic acid and Zn(NO3)2·6H2O were dissolved in an acetonitrile aqueous solution with a volume concentration of 70% in a molar ratio of 1:2.5. Stir at room temperature for 30 minutes to mix evenly, and then transfer the mixed solution to a 20mL Teflon reactor. After drying the reactor in a constant temperature oven at 150°C for 90 hours, cool it to room temperature, grind it, and obtain a zinc-based metal organic framework material. The mass percentage of each element in the zinc-based metal organic framework material of this embodiment is: Zn: 24.98%, C: 53.45%, N: 5.72%, O: 15.85%. Then, using 340nm ultraviolet light as excitation, obtain the solid-state fluorescence spectrum of the zinc-based metal organic framework material in Example 2.
[0060] (II) Preparation of highly conductive liquid metal composite materials
[0061] The eutectic gallium-indium alloy was poured into a beaker and ultrasonically stirred for 45 seconds, and then the zinc-based metal organic framework material prepared in this embodiment (I) was dispersed in the eutectic gallium-indium alloy, and ultrasonically stirred for 65 seconds to obtain a highly conductive liquid metal composite material, and finally the highly conductive liquid metal composite material was transferred to a culture dish for storage. In this embodiment, the mass ratio of the zinc-based metal organic framework material to the liquid metal when mixed was 1:200.
[0062] Example 3
[0063] (I) Preparation of Zn-based Metal-Organic Framework Materials
[0064] The solid powders of 5-((4'-(tetrazolyl-5'-yl)benzyl)oxy)isophthalic acid and Zn(NO3)2·6H2O were dissolved in an acetonitrile aqueous solution with a volume concentration of 65% in a molar ratio of 1:2.4. Stir at room temperature for 30 minutes to mix evenly, and then transfer the mixed solution to a 20mL Teflon reactor. After drying the reactor in a constant temperature oven at 140°C for 100 hours, cool it to room temperature, grind it, and obtain a zinc-based metal organic framework material. The mass percentage of each element in the zinc-based metal organic framework material of this embodiment is: Zn: 24.23%, C: 53.70%, N: 5.92%, O: 16.15%. Then, using 340nm ultraviolet light as excitation, obtain the solid-state fluorescence spectrum of the zinc-based metal organic framework material in Example 3.
[0065] (II) Preparation of liquid metal composite materials
[0066] The eutectic gallium-indium alloy was poured into a beaker and ultrasonically stirred for 50 seconds, and then the zinc-based metal organic framework material prepared in this embodiment (I) was dispersed in the eutectic gallium-indium alloy, and ultrasonically stirred for 70 seconds to obtain a highly conductive liquid metal composite material, and finally the highly conductive liquid metal composite material was transferred to a culture dish for storage. In this embodiment, the mass ratio of the zinc-based metal organic framework material to the liquid metal when mixed was 1:300.
[0067] The electrical conductivity of the high-conductivity liquid metal composite materials in Examples 1-3 was tested respectively, and the results were as follows: Figure 5 As shown, Figure 5 In the figure, the horizontal axis represents the mass ratio of the liquid metal to the zinc-based metal organic framework material in Examples 1-3, and the vertical axis represents the conductivity. Figure 5 It can be seen that the liquid metal composite material in the embodiment of the present invention has excellent electrical conductivity, specifically at 2.5×10 6 Near S / m.
[0068] Comparative Example 1
[0069] In this comparative example, 340 nm ultraviolet light was used as excitation to obtain a solid-state fluorescence spectrum of 5-((4'-(tetrazolyl-5'-yl)benzyl)oxy)isophthalic acid.
[0070] Comparative Example 2
[0071] In this comparative example, solid powders of terephthalic acid and Zn(NO3)2·6H2O are dissolved in an acetonitrile aqueous solution with a volume concentration of 62.5% in a molar ratio of 1:2. Stir at room temperature for 30 minutes to mix evenly, and then transfer the mixed solution to a 20mL Teflon reactor. After the reactor is placed in a constant temperature oven at 120°C and dried for 96 hours, it is cooled to room temperature and ground to obtain a zinc-based metal organic framework material. Then, a solid-state fluorescence spectrum of the zinc-based metal organic framework material in comparative example 2 is obtained using 340nm ultraviolet light as excitation.
[0072] Comparative Example 3
[0073] In this comparative example, solid powders of 5-((4'-(tetrazolyl-5'-yl)benzyl)oxy)isophthalic acid and Mn(NO3)2·6H2O were dissolved in an acetonitrile aqueous solution with a volume concentration of 62.5% at a molar ratio of 1:2. Stir at room temperature for 30 minutes to mix evenly, and then transfer the mixed solution to a 20mL Teflon reactor. After drying the reactor in a constant temperature oven at 120°C for 96 hours, cool it to room temperature, grind it, and obtain a manganese-based metal organic framework material. Then, using 340nm ultraviolet light as excitation, obtain the solid-state fluorescence spectrum of the manganese-based metal organic framework material in Comparative Example 3.
[0074] The solid-state fluorescence spectra of each material in Examples 1-3 and Comparative Examples 1-3 are summarized as follows: Figure 6 shown. Figure 6 The vertical axis represents the relative magnitude of the spectral intensity of different materials, not a specific physical quantity. Figure 6It can be seen that when excited by 340nm ultraviolet light, the solid-state fluorescence spectrum of the zinc-based metal organic framework material in Examples 1-3 is concentrated near 480nm, the solid-state fluorescence spectrum of the single organic ligand in Comparative Example 1 is concentrated at 342nm, the solid-state fluorescence spectrum of the zinc-based metal organic framework material in Comparative Example 2 is concentrated near 460nm, and the solid-state fluorescence spectrum of the manganese-based metal organic framework material in Comparative Example 3 is concentrated near 480nm. Since the visible light range observed by the normal human eye is 380-700nm, compared with the single organic ligand in Comparative Example 1, the metal organic framework materials in Examples 1-3 and Comparative Examples 2-3 are all red-shifted, achieving fluorescence visualization. Further, compared with Comparative Examples 2-3, the fluorescence intensity of the zinc-based metal organic framework materials in Examples 1-3 is significantly improved. It can be seen from the figure that the fluorescence intensity of Examples 1-3 is about twice that of Comparative Example 1, and about twice that of Comparative Examples 2 and 3.
[0075] Since the d orbital electrons of zinc are full, in the process of forming a metal organic framework, the coordination number and stereo configuration of the central metal are less affected by the coordination field, so a variety of coordination modes can be generated, and it is easier to form a three-dimensional framework, which is more conducive to further improvement of fluorescence, adsorption and other properties. Compared with a single organic ligand, the metal organic framework material obtained by the present invention has a fluorescence intensity that is more than 2 times stronger, and at the same time, the rigidity and coplanarity are significantly increased, and the structure is more stable.
[0076] Comparative Example 4
[0077] The liquid metal composite material in this comparative example is derived from lm Ink in the open journal "Ultrasonic non-destructive and substrate-independent sintering of liquid metal inks" (DOI: 10.1002 / advs.202301292).
[0078] Comparative Example 5
[0079] The liquid metal composite material in this comparative example is derived from CLPRGG in the open journal "Cellulose nanofiber liquid metal hydrogel with high tensile strength, environmental adaptability and electromagnetic shielding function for temperature monitoring and strain sensor" (Carbohydrate Polymers 348 (2025) 122788).
[0080] Comparative Example 6
[0081] The liquid metal composite material in this comparative example is derived from HD-LMC in the open journal "Deformable 3D Curved High-Density Liquid Metal Coil-Integrated Unit for Universal Soft Actuation, Sensing and Communication" (Nature Communications|(2024)15:7679).
[0082] Comparative Example 7
[0083] The liquid metal composite material in this comparative example is derived from MLM-D in the open journal "Stretchable, printable, adhesive, highly conductive MXene liquid metal putty with improved wettability" (Nature Communications|(2024)15:6138).
[0084] The conductivity comparison of the composite materials lm Ink, CLPRGG, HD-LMC and MLM-D in Comparative Examples 4-7 and the high conductivity liquid metal composite material in Example 1 is shown in the figure below: Figure 7 As shown. Figure 7 It can be seen that after the liquid metals in Comparative Examples 4-7 are compounded with other materials, the conductivity of the composite materials decreases, and they are all lower than the high-conductivity liquid metal composite material in Example 1 of the present invention. This shows that compared with the phenomenon that the conductivity of the composite material decreases after adding related polymers to the liquid metal, the zinc-based metal organic framework material in the embodiment of the present invention is compounded with the liquid metal, which can effectively maintain the high conductivity of the liquid metal.
[0085] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A highly conductive liquid metal composite material, characterized in that: The highly conductive liquid metal composite material comprises a zinc-based metal organic framework material and liquid metal, and the zinc-based metal organic framework material is prepared by the following method: The zinc salt and 5-((4'-(tetrazolyl-5'-yl)benzyl)oxy)isophthalic acid are dissolved in a reaction solvent, stirred and mixed evenly, dried, cooled to room temperature, and ground to obtain a zinc-based metal organic framework material.
2. The highly conductive liquid metal composite material according to claim 1, characterized in that: The zinc-based metal organic framework material includes the following elements in percentage by mass: C: 50% to 55%, N: 5% to 7%, O: 15% to 20%, and Zn: 20% to 25%.
3. The highly conductive liquid metal composite material according to claim 1, characterized in that: The particle size of the zinc-based metal organic framework material is between 40 μm and 200 μm.
4. The highly conductive liquid metal composite material according to claim 1, characterized in that: The molar ratio of the zinc salt to the 5-((4'-(tetrazol-5'-yl)benzyl)oxy)isophthalic acid is 2:1 to 2.5:
1.
5. The highly conductive liquid metal composite material according to claim 1, characterized in that: The reaction solvent is an acetonitrile aqueous solution, and the volume concentration of the acetonitrile aqueous solution is 50% to 70%; And / or, the zinc salt is zinc nitrate, zinc chloride, zinc acetate and corresponding crystalline hydrated zinc salt.
6. The highly conductive liquid metal composite material according to claim 1, characterized in that: The drying comprises: drying at 120° C. to 150° C. for 90 hours to 100 hours.
7. The highly conductive liquid metal composite material according to claim 1, characterized in that: The liquid metal includes eutectic gallium-indium alloy and / or eutectic gallium-indium-tin alloy.
8. A method for preparing a highly conductive liquid metal composite material, for preparing the liquid metal composite material as claimed in any one of claims 1 to 7, characterized in that: include: The liquid metal is first ultrasonically stirred for 40s to 50s, and then the zinc-based metal organic framework material is mixed with the liquid metal and ultrasonically stirred for 60s to 70s to obtain a liquid metal composite material.
9. The method for preparing a highly conductive liquid metal composite material according to claim 8, characterized in that: The mass ratio of the zinc-based metal organic framework material and the liquid metal when mixed is 1:(100-300).
10. Use of the highly conductive liquid metal composite material according to any one of claims 1 to 7 in flexible wearable devices.